Eficiência do tratamento parcial de bovinos infestados por mosca-dos-chifres utilizando diazinon 40% - de Almeida, Fabiana Alves [UNESP]; Alari, Fernando de Oliveira [UNESP]; Seno, Maria Conceição Zocoller [UNESP]; de Lima, Marco Monteiro [UNESP]; Nascimento, Sheila Tavares [UNESP]; Neto, Marcos Chiquitelli [UNESP] (My University, 2013)
The aim of this investigation was to evaluate the efficiency of partial treatment of animals infested with horn flies. Forty-five Guzerat cows between 4 and 7 years of age were divided into three groups (15 cows per group). The treatments were as follows: in groups G33 and G100, 33.3 and 100% of the cows were treated with one insecticide-impregnated ear tag/animal (40% diazinon), respectively, while in the group GC, the cows were not treated (control). The flies on the cervico-dorsal-lumbar region of the cows, in all three groups, were counted every 14 days. The experiment lasted from September 2006 to September 2009. Over this period, six four-month ear tag treatments, with intervals of one to two months, were conducted on both treated groups. The animals of group G33 had a higher infection than those of group G100, and the number of flies ranged from 12 to 27 (group G33) and from 3 to 11 (group G100). However, groups G33 and G100 had lower infection levels than group GC, which presented from 45 to 87 flies. Partial treatment of cattle infested with horn flies using 40% diazinon insecticide is an efficient alternative for controlling this ectoparasite.
Efficiency of partial treatment of cattle infested with horn fly using 40% diazinon
Keywords: Horn flies; Organophosphate; Selective control